2013
DOI: 10.1021/ct400476r
|View full text |Cite
|
Sign up to set email alerts
|

Band Gaps and Optical Spectra of Chlorographene, Fluorographene and Graphane from G0W0, GW0 and GW Calculations on Top of PBE and HSE06 Orbitals

Abstract: The band structures of three graphene derivatives (chlorographene, fluorographene, and graphane) were analyzed at three levels of many-body GW theory (G0W0, GW0, and GW) constructed over GGA (PBE) and screened hybrid HSE06 orbitals. DFT band gap values obtained with the HSE06 functional were notably larger than those from PBE calculations but were significantly lower than band gaps from all GW calculations. On the other hand, all GW-type calculations gave similar band gaps despite some differences in band stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
146
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 52 publications
21
146
0
Order By: Relevance
“…3(b). The optical gap is 5.67 eV, consistent with the values of 5.4 eV ~ 5.6 eV from two previous GW-BSE studies [20,21]. These values are much higher than the lower limit of ~3.8 eV measured in a recent experiment [18], while a separate GW-BSE study reported almost the same optical gap as experimentally observed [22].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…3(b). The optical gap is 5.67 eV, consistent with the values of 5.4 eV ~ 5.6 eV from two previous GW-BSE studies [20,21]. These values are much higher than the lower limit of ~3.8 eV measured in a recent experiment [18], while a separate GW-BSE study reported almost the same optical gap as experimentally observed [22].…”
supporting
confidence: 88%
“…These values are much higher than the lower limit of ~3.8 eV measured in a recent experiment [18], while a separate GW-BSE study reported almost the same optical gap as experimentally observed [22]. As discussed previously [20,21,34], the discrepancy in the optical gap between theory and experiment could be ascribed to the [33]. In Fig.…”
supporting
confidence: 55%
“…As shown in Figure 9 , graphene had many notable peaks around 10–12 eV as a result of strong electron–hole correlations along with the appearance of bounded excitons in the ultraviolet region, opening the path toward an excitonic Bose‐Einstein condensate in graphene that was observed experimentally. [[qv: 12b]],56, 58 This feature was also obtained for fluorographene. A distinctive peak around 9.8 eV of fluorographene emerged in GW‐BSE that was evidently connected to strong electron‐hole coupling and was attributed to the transition from the near‐gap valence bands to the minimum conduction band.…”
Section: Propertiesmentioning
confidence: 58%
“…According to our DFT results using the both functionals, the band-gap remains almost unchanged up to a high strain of 2/3ɛ uts . However, , we however emphasis that in the future studies more elaborated hybrid functionals such as GW [56][57][58][59][60] should be employed to discuss the electronic structure of C 3 N nanomembranes under different loading conditions. Thermal stability of a material at high temperatures is among the appealing properties for the practical applications.…”
Section: Resultsmentioning
confidence: 99%